Evaluasi Risiko Ergonomi dengan Analisis Postur Tubuh untuk Mengurangi Keluhan Musculoskeletal Disorders pada Pekerja - Cindy Laurinda (Universitas Bunda Mulia, 2021)
The economy is an important thing in a country, without an economy, a country can't run. The economy of a country is certainly supported by an industrial sector, one of which is the metal and iron processing industry. Workers in the company will certainly have regulations that will regulate the workforce when doing work at the company. PT. Smart Teknik Utama Bandung is a company engaged in the processing of metal, iron, and others that produces various products derived from iron and plates. The main product of this company is Roding China. The company has a problem, namely the work posture of the employees on the production floor. Wrong work posture results in MSDs complaints among workers which reduce the quality of workers. The purpose of this research is to analyze the work posture used by the workforce is already ergonomic or not. Work posture analysis used the Nordic Body Map method, Ovako Work Posture Analysis, and Rapid Entire Body Assessment. The analysis was carried out on 12 employees from 7 workstations. With the analysis carried out, it is known that all employees have MSDs complaints which are caused by incorrect and unergonomic work postures, then suggestions are given to improve work posture to reduce MSDs complaints experienced by employees.